Enhancing Photosynthesis with Carbon Dots: A Review of Recent Research - Usenko, Stanislav; Shapovalov, Yevhenii; Salyuk, Anatoly (My University, 2023)
Вуглецеві точки розглядаються як перспективний інструмент для підвищення фотосинтезу та збільшення врожайності сільськогосподарських культур. Останні дослідження показали, що вуглецеві точки здатні покращувати поглинання світла і перенесення енергії, приводячи до загального підвищення ефективності фотосинтезу. Хоча механізми впливу ще вивчаються, потенційні можливості для сталого агровиробництва є значними. Подальші дослідження необхідні для повної реалізації цього потенціалу. Carbon dots have emerged as a promising tool for improving photosynthesis and increasing crop yields. Recent research has demonstrated that carbon dots can enhance light absorption and energy transfer in plants, leading to an overall increase in photosynthetic efficiency. While the mechanisms by which carbon dots improve photosynthesis are not yet fully understood, their potential applications in sustainable agriculture are significant. Further research is needed to fully realize the potential of carbon dots in improving photosynthesis.
Keywords: carbon dots; вуглецеві точки; photosynthesis; фотосинтез; стале сільське господарство; кафедра харчової хімії